Penerapan E-Filing Dalam Meningkatkan Kesadaran Hukum Wajib Pajak Orang Pribadi (Studi Kantor Pelayanan Pajak Pratama Madiun) - Subadi; Taufiq Yuli Purnama; Zulfa Rahima Cahyasari; angga pramodya pradhana (Universitas Merdeka Madiun, 2022)
Abstract–The purpose of this study is to determine the application of e-filing as a means of increasing legal awareness for taxpayers, especially individuals and to find out the supporting factors and obstacles in implementing e-filing for the Madiun area. In this study, the researcher used empirical methods, namely data obtained directly through field research with primary data sources, secondary data sources and tertiary data sources and data collection techniques carried out by observation, interviews, document studies to informants using qualitative descriptive data analysis. The results of this study indicate that the implementation of e-filing at the Pelayanan Pajak Pratama (KPPP) Madiun Office is going well and has increased almost every year, with many benefits that make it easier for KPP and taxpayers, especially during this pandemic, although there are some shortcomings, especially in terms of socialization about e-filing and the down system that occurs in its implementation. However, the other stages and contents have been carried out well, especially in the implementation of e-filing. There are 2 (two) benefits in this research, namely practical and theoretical, practically to develop legal knowledge and add references for readers, theoretically in KPPP Madiun can be used as input in order to increase the application of e-filing in mandatory legal awareness taxes to be a good and practical solution in reporting the Annual SPT. Keywords: e-filing, Taxpayer, Kantor Pelayanan Pajak Pratama Madiun.